SQUARE OF THE ERROR OCTONIONIC THEOREM AND HYPERCOMPLEX FOURIER SERIES - Martinez, C. A. P.; Martinez, André L. M.; Borges Neto, Manoel Ferreira; Castelani, Emerson Vitor (Trends in Computational and Applied Mathematics, 2013)
The focus of this paper is to address some classical results for a class of hypercomplex numbers. More specifically we present an extension of the Square of the Error Theorem and a Bessel inequality for octonions.